Evaluation of the Physical Work Environment of Miners in Kutai Kartanegara, East Kalimantan - Putri Pujianti; Zulkifli Djunaidi (The Indonesian Journal of Occupational Safety and Health, 2022)
Introduction: Mining is a field of work that has a high potential of risk, both in terms of health risks and safety risks. In its business processes, environmental factors are one of the potential risks that cannot be avoided by every employee. Physical work environment factors are everything around the workplace that can affect workers, either directly or indirectly, and can cause health problems such as headaches, dizziness, nausea, shortness of breath, fatigue, and dehydration. This study aims to determine the physical environmental factors that greatly influence employee productivity. Methods: This study used quantitative methods and the secondary data. Measurement of physical factors applied the standard Threshold Limit Value (TLV) in accordance with the Regulation of the Minister of Manpower of the Republic of Indonesia Number 05 of 2018. Measurements were carried out in the workshop areas, ports, heavy equipment units, and office spaces of each department. In this study, measurements of physical climate include work climate, placement, and lighting. Results: The physical work environment is found to be good enough despite being below the standard in some areas, e.g., the lighting at the administration desk, the noise in the generator room, and some heavy equipment such as bulldozers and dump trucks. Conclusions: The physical work environment is still considered safe and will not cause health problems. However, the arrangement of lighting conditions, work climate, and noise can be improved to meet the overall OHS standards and the evaluation of other work environment factors.Keywords: literature review, metal industry, occupational contact dermatitis.